SEJARAH PRAKTIK PENGGUNAAN MANTRA DALAM MASYARAKAT KERINCI BERDASARKAN NASKAH TAMBO DAN KITAB AZIMAT KERINCI - Yova Sandra; Egi Gianturi; Wulandari Nurul Utami; Yulfira Riza (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
Incung script is the original Kerinci script written on horns, animal skin, bark, Daluang leaves, and paper. This article aims to identify the style of script writing and the use of mantras in Kerinci community such as for treatment, immunity, defense, and other function based on Kerinci’s Tambo script and Azimat manuscript. This paper uses historical research methods with philological and textological approaches. The result of this study indicates that the Kerinci’s people used it before the arrival of Islam. It continued after the arrival of Islam. It can be seen from the presence of Islamic words such as Muhammad, Allah, and so on. In addition, the use of mantras in Kerinci’s community is quite varied, including as a strategy in defending Ulayat lands or fighting with Duwak (mysticism spell), Cuco (ancestral spirit summoning spell) and so on. Mantra and it funtion have been written in manuscripts by Kerinci’s community.